Produk Oksidasi Lemak Salah Satu Penyebab Penyakit Jantung Koroner - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Food consumer have been advised to reduce fat and cholesterol intake, because high fat and cholesterol consumption has been known as a risk factor of Coronary Heart Disease (CHD). However, there are patients with CHD and their serum cholesterol levels are surprisingly normal, while there are group of people with relatively high serum cholesterol levels but they are perfectly healthy. Therefore, this review is intended to stimulate new thinking to find other possible mechanisms to explain the existing anomalies from the commonly known Lipid Hypothesis. Chronic consumption of foods containing lipid oxidation products in combination with lack of dietary antioxidant intake could lead to higher risk of getting CHD.